Job Performance and Job Satisfaction of Veterinary Personnel in Kerala - Jayachandran S (Department Of Extension, College Of Veterinary And Animal Sciences, 1992)
The objectives of the study were to assess the level of job satisfaction of veterinary personnel in carrying out their official functions, to identify the constraint factors pertaining to their job and to assess the problems and solutions related to the job performance as perceived by them. The study was conducted among the veterinary surgeons in the Animal Husbandary Department of Kerala. The data were collected through mailed questionannaire method using a pre tested schedule. Variables were measured using appropriate sales and suitable statistical tools were used for analising the data. In general for the most of the socio-personal and psychological characteristics and organizational factors the responds belonged to the medium category. Job performance as Veterinary Doctor and as Cattle Improvement Officer, majority were in the medium and high performance group. As supervisor majority were in the medium performance group. Majority of the respondents had medium level of job satisfaction. Self esteem, organizational commitment and organizational climate were positively and significantly correlated with job satisfaction. Communication ability, job autonomy and personal importance were positively and significantly (at 5% level) correlated with job satisfaction. Other variables had non-significant relationship with job satisfaction. Job performance as Veterinary Doctor was positively and significantly correlated with job satisfaction. As Cattle Improvement Officer and Supervisor job performance had positive but non-significant correlation with job satisfaction. Lack of adequate funds and delay in sanction for purchase of essential items were the most important administrative problems. Inadequate supply of medicines and lack of equipments were the important technical problems. Treatment by non-qualified persons and lack of facilities for examination of clinical materials were the important problems faced in the area of nature of work. Difficulty in arranging loan to farmers and supervising repayment of loan were the problems faced in planning and execution of work.